Healthy eSport Engagement for eSport Athletes: A Proposal for A Research Framework - Khir, Masrur Mohd; Maon, Siti Noorsuriani; Demong, Nur Atiqah Rochin (Journal of Entrepreneurship, Business and Economics, 2022)
The global spread of Covid19 poses a challenge to the business landscape at a magnitude we have not seen before. Covid19 was declared a “public health emergency of international concern” by the International Health Regulations Emergency Committee of the World Health Organization (WHO) on January 30, 2020. Less than two months later, the WHO declared COVID-19 as a pandemic. The situation of lockdown and movement restrictions has resulted in the emergence of online related activities on digital platforms such as online businesses, online learning and also the online gaming that is now known as eSport. Online gaming or eSport has become very popular among the public, including university students. Hence, excessive involvement in eSport activities will have negative effects not only to the students’ health but also to their quality of life. Despite a growing research interest in eSport, a void knowledge exists regarding the healthy eSport lifestyle. To address the gap in research, this paper aims to take an initial step by proposing a framework for a holistic model to determine the attributes of a balanced quality of life for eSport athletes. The framework combines two approaches from both health and sports literature and methodically will be using both qualitative and quantitative approaches for its investigation. The framework can help eSports athletes, especially students, to maintain a balanced quality of life despite their engagement in eSport activities. Research paper Keywords: eSport; healthy engagement; quality of life; lifestyle; athletes Reference to this paper should be made as follows: Khir, M. M., Maon, S. N., & Demong, N. A. R. (2022). Healthy eSport Engagement for eSport Athletes: A Proposal for A Research Framework. Journal of Entrepreneurship, Business and Economics , 10 (2), 110–126.